Antecedents of Entrepreneurial Intention: The Impacts of Entrepreneurial Knowledge, Entrepreneurial Mindset, and Entrepreneurial Alertness - Heryatno, Roni; Hidayat, Desman; Kusumaningtyas, Ary Wijayati; Ali, Hapzi (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
Entrepreneurship can be a way to improve Indonesia’s economic, social, and environmental condition. This study aims to understand the relationship between entrepreneurial knowledge, entrepreneurial mindset, entrepreneurial alertness, and entrepreneurial intention. A total of 100 university students in the Greater Jakarta region in Indonesia were chosen as the respondents of this study. The results of this study showed that entrepreneurial intention is affected directly by entrepreneurial alertness. It is also affected indirectly by entrepreneurial mindset when it is mediated by entrepreneurial alertness. However, there are no direct effects on entrepreneurial mindset and entrepreneurial knowledge toward entrepreneurial intention. Moreover, both entrepreneurial mindset and entrepreneurial knowledge have positive and significant effect towards entrepreneurial alertness. This study gives an empirical and theoretical results basis for the antecedents of entrepreneurial intention.